2018
DOI: 10.2147/ijn.s181855
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism research on a bioactive resveratrol–PLA–gelatin porous nano-scaffold in promoting the repair of cartilage defect

Abstract: BackgroundArticular cartilage defects are difficult to treat, but drug-loaded tissue engineering scaffolds provide a possible treatment option for these types of injuries.PurposeIn this study, we designed a bioactive resveratrol–PLA–gelatin porous nano-scaffold using electrospinning, freeze drying, and uniform dispersion techniques to repair articular cartilage defects, and then investigated the possible mechanism behind the successful repair.MethodsWe established an articular cartilage defect rat model with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…are used to repair cartilage defects. However, if grafts do not fuse well with regeneration and subchondral bone, the treatment effect is usually poor (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…are used to repair cartilage defects. However, if grafts do not fuse well with regeneration and subchondral bone, the treatment effect is usually poor (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate osseointegration of titanium implants,46 there have been proposed coatings, such as hydroxyapatite (HAP), collagen (COL), other extracellular matrix proteins and even autologous osteoblasts, that were suitable to enhance bone healing and regeneration 712. The HAP/COL composites were used on rabbits to demonstrate their ability to heal osteochondral defects,13 showing active bone tissue formation 14…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in another study on femur healing histomorphometrically and to evaluate the effects of resveratrol on negative effects of cigarette smoke showed that areas of new bone formation in the resveratrol and control groups were higher than in the smoking and smoking+resveratrol groups of rats that were given 20 mg/kg body weight resveratrol 40 . Apart from these, the effects of resveratrol cell culture models in relation to bone tissue were investigated in different studies 41 43 .…”
Section: Discussionmentioning
confidence: 99%